2002
DOI: 10.1063/1.1472476
|View full text |Cite
|
Sign up to set email alerts
|

Structure and piezoelectric properties of sol–gel-derived 0.5 Pb[Yb1/2Nb1/2]O3–0.5 PbTiO3 thin films

Abstract: 0.5 Pb[Yb1/2Nb1/2]O3–0.5 PbTiO3 thin films were deposited on (111) Pt/Ti/SiO2/Si substrates by sol–gel processing using a thin Pb(Zr0.52Ti0.48)O3 seed layer. X-ray diffraction analysis and scanning electron microscopy revealed that the films were strongly (111) oriented, mimicking the orientation of the (111) Pt/Ti/SiO2/Si substrate. No pyrochlore phase was observed by x-ray diffraction and the films had a uniform grain size of about 50–60 nm. The dielectric permittivity and loss factor varied only slightly wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…A pMUT is a device able to transmit and receive ultrasonic waves. Potential applications are [73][74][75]. The values derived from ceramics data refer to early PZT ceramics [76], standard hard PZT 4 (product of Morgan Electroceramics), and modern optimized PZT ceramics, the 3203 of Motorola.…”
Section: Basics Of Micromachining and Piezoelectric Thin Film Structuresmentioning
confidence: 99%
“…A pMUT is a device able to transmit and receive ultrasonic waves. Potential applications are [73][74][75]. The values derived from ceramics data refer to early PZT ceramics [76], standard hard PZT 4 (product of Morgan Electroceramics), and modern optimized PZT ceramics, the 3203 of Motorola.…”
Section: Basics Of Micromachining and Piezoelectric Thin Film Structuresmentioning
confidence: 99%
“…[12][13][14] A chemical solution deposition ͑CSD͒ process for ͑111͒-oriented films on a Si substrate was recently reported. 15 In this work, the fabrication of ͑001͒-oriented 0.5PYbN-0.5PT thin films deposited onto (111)Pt/Ti/SiO 2 /Si substrates by sol-gel processing is reported. The textures of the films are monitored as a function of heating rate, annealing temperature, and film thickness.…”
Section: Introductionmentioning
confidence: 99%
“…* Corresponding author. The investigations of the PYN-PT system have been concentrated to the MPB compositions up to now [7][8][9][10], because several properties exhibit the maximum at the MPB. However, Foster et al and Oikawa et al reported on the ferroelectricity of the MOCVD-derived PZT films with different Zr:Ti ratios [11,12].…”
Section: Introductionmentioning
confidence: 99%